PERLINDUNGAN HUKUM BAGI ANAK KORBAN TINDAK PIDANA PELECEHAN SEKSUAL (Faculty of Law, University of Dr. Soetomo, 2019)
Moral crime or moral harassment and sexual harassment are two forms of violation of morality which are not only a national legal problem of a country, but already a legal problem of all countries in the world or a global problem. The research method used by the author is a type of normative legal research with the legislation approach and concept approach. The goal to be achieved is to realize optimal legal protection for child victims of sexual abuse, which has many problems. The results showed that legal protection for child victims of sexual abuse was carried out by providing legal assistance and rehabilitation. The implementation of legal protection is still constrained by the substance of the law; legal structure, legal culture, facilities and infrastructure. A clear and comprehensive regulation on the protection of children which in essence aims to provide guarantees and protect their rights so that they can live, grow, develop and participate, optimally, and obtain protection from violence and discrimination.Keywords : Legal Protection, Children, Sexual Harassment